Adversity Qoutient dan Character Strength terhadap Resiliensi Penduduk di Pemukiman Kumuh Batang Arau Padang - Rina Mariana; Isna Asyri Syahrina; Nina Zulida Situmorang; Ahmad Muhammad Diponegoro (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2022)
In Indonesia there are still many people who live in slums, due to various factors. This is of course a shared responsibility and needs more attention, especially from the government and from various circles. Many things happen and affect the condition of people who live in slums, because in terms of health it is also different from those who live in livable settlements. The purpose of the study was to determine whether there is a role for Adversity Qoutient and Character Strength on the resilience of residents in Slum Settlement in the Batang Arau area, Padang City. The research subjects were 110 residential residents aged 25-60 years. Adversity Qoutient is measured by Stoltz's Adversity Quotient (AQ) scale, VIA-Character Strength is measured by Peterson and Seligman's VIA-Character Strength scale, and resilience is measured by Reivich and Shatte's resilience scale. The data was processed by multiple regression analysis method using SPSS version 23.00 for windows. Based on the results of the correlation test, it is known that there is a positive and significant correlation between adversity quotient and resilience (p = 0.000), then there is a positive and significant correlation between character strength and resilience (p = 0.000), and positive and significant correlations. significant relationship between adversity quotient and character strength (AQ) (p = 0.044). The results of this study prove that Adversity Qoutient and Character Strength together play a role in resilience. Adversity Qoutient and Character Strength together make an effective contribution of 56%. The conclusion is to increase the resilience of the population in the slum area of ​​Batang Arau Padang by increasing the Adversity Qoutient and Character Strength.